3D GOVERNMENT ENTERPRISE ARCHITECTURE FRAMEWORK - Firmansyah, Gerry (JIK: Jurnal Ilmu Komputer, 2017)
AbstractBased on the research on the determinants of successful e-Government implementation that have been studied the results are very diverse, in the previous study using Principal Component Analysis found an inherent structure that became the main component of e-Government implementation, each component has a weight. When resource constraints (time, cost, sdm) then weights can help in determining the priorities of e-government implementation. Inherent structure combined with Generic Government Enterprise Architecture can form a new 3D Governance Enterprise Architecture (GEA) that becomes the reference of a country. This research performs GEA formation process by using inherent structure of e-government data. Keywords: e-government, e-government component, principal component analysis AbstrakBerdsarkan penelitian mengenai faktor penentu keberhasilan implementasi e-Government yang sudah dipelajari hasilnya sangat beragam, pada penelitian sebelumnya dengan menggunakan Principal Component Analysis ditemukan suatu inherent structureyang menjadi komponen utama dari implementasi e-Government, setiap komponen mempunyai bobot. Saat keterbatasan sumber daya (waktu, biaya, sdm) maka bobot dapat membantu dalam menentukan prioritas implementasi e-government. Inherent structure yang dikombinasikan dengan Generic Government Enterprise Architecture dapat membentuk suatu 3D Government Enterprise Architecture (GEA) baru yang menjadi acuan dari sebuah negara. Penelitian ini melakukan proses pembentukan GEA dengan menggunakan inherent structure dari data e-government. Kata Kunci: e-government, e-government component, principal component analysis